The effect of comprehensive intervention for childhood obesity on dietary diversity among younger children: Evidence from a school-based randomized controlled trial in China. - Haiquan Xu; Olivier Ecker; Qian Zhang; Songming Du; Ailing Liu; Yanping Li; Xiaoqi Hu; Tingyu Li; Hongwei Guo; Ying Li; Guifa Xu; Weijia Liu; et al. (PLoS ONE)
Background Little evidence from developing countries on dietary transition demonstrates the effects of comprehensive childhood obesity interventions on dietary diversity and food variety among younger children. This study aimed to evaluate the effects of comprehensive childhood obesity interventions on dietary diversity among younger children. Methods A total of 4846 children aged 7-13 years were included based on a multicenter randomized controlled trial for childhood obesity interventions in 38 primary schools. Nutrition education intervention (NE), physical activity intervention (PA) and comprehensive intervention including both NE and PA (CNP) were carried out separately for 2 semesters. Dietary Diversity Score (DDS9 and DDS28 for 9 and 28 food groupings, respectively), Food Variety Score (FVS, the number of food items) and the proportions of different foods consumed were calculated according to the food intake records collected with the 24-h dietary recall method. Results The intervention effects per day of comprehensive intervention group were 0 (95% Confidence Interval (CI): 0, 0.1; p = 0.382) on DDS9, 0.1 (95% CI: -0.1, 0.2; p = 0.374) on DDS28 and 0.1 (95% CI: -0.1, 0.3; p = 0.186) on FVS of overall diet, which was 0.1 (95% CI: 0, 0.1; p < 0.001) on DDS9, 0 (95% CI: 0, 0.1; p = 0.168) on DDS28 and 0.1 (95% CI: 0, 0.1; p = 0.067) on FVS of dietary scores of breakfast only. Additionally, CNP group had greater increases in cereals, meat and fruits, and more decreases in eggs, fish and dried legumes consumption proportions as compared with the control group. Decreasing side effect on dietary diversity and food variety were found for PA intervention, but not for NE intervention only. Conclusions Though the comprehensive obesity intervention didn't improve the overall dietary diversity per day, the positive intervention effects were observed on breakfast foods and some foods' consumption.